American dirt (oprah's book club) eaudiobook A novel. - Cummins, Jeanine (Macmillan Audio, 2020)
#1 New York Times Bestseller OPRAH'S BOOK CLUB PICK " Extraordinary ."— Stephen King "This book is not simply the great American novel; it's the great novel of las Americas . It's the great world novel! This is the international story of our times. Masterful."—Sandra Cisneros También de este lado hay sueños. On this side too, there are dreams . Lydia Quixano Pérez lives in the Mexican city of Acapulco. She runs a bookstore. She has a son, Luca, the love of her life, and a wonderful husband who is a journalist. And while there are cracks beginning to show in Acapulco because of the drug cartels, her life is, by and large, fairly comfortable. Even though she knows they'll never sell, Lydia stocks some of her all-time favorite books in her store. And then one day a man enters the shop to browse and comes up to the register with a few books he would like to buy—two of them her favorites. Javier is erudite. He is charming. And, unbeknownst to Lydia, he is the jefe of the newest drug cartel that has gruesomely taken over the city. When Lydia's husband's tell-all profile of Javier is published, none of their lives will ever be the same. Forced to flee, Lydia and eight-year-old Luca soon find themselves miles and worlds away from their comfortable middle-class existence. Instantly transformed into migrants, Lydia and Luca ride la bestia —trains that make their way north toward the United States, which is the only place Javier's reach doesn't extend. As they join the countless people trying to reach el norte , Lydia soon sees that everyone is running from something. But what exactly are they running to? American Dirt will leave listeners utterly changed. It is a literary achievement filled with poignancy, drama, and humanity. It is one of the most important books for our times. Already being hailed as "a Grapes of Wrath for our times" and "a new American classic," Jeanine Cummins's American Dirt is a rare exploration into the inner hearts of people willing to sacrifice everything for a glimmer of hope. "Narrator Yareli Arizmendi illuminates the humanity and individuality of Latin American migrants as they flee toward refuge in the North..The account of Lydia and Luca's travails, including terrifying rides atop Mexico's freight trains, is utterly compelling. But it is Arizmendi's voicing of Lydia, so full of fierce tenderness, that will stay with listeners after the story's close."— AudioFile Magazine